A reflective analysis on the inequities in cancer diagnosis and treatment in Latin America: a call to action for public health - Gabriela Guerron-Gomez; Mariana Rojas-Fierro; Rafael Parra-Medina; Andrés Mosquera; Marcela Gomez Suarez (International Journal for Equity in Health)
Abstract Cancer continues to be a significant public health challenge in Latin America and the Caribbean (LAC), marked by rising incidence and mortality rates and a projection of increased burden by 2040. Despite the recognized importance of early diagnosis and treatment, the LAC region faces profound disparities in cancer care access due to socioeconomic, geographic, and educational barriers. These inequities are exacerbated by a lack of medical specialists, healthcare access limitations, and the distribution of resources, especially in rural areas. Social determinants of health (SDH) such as income level, educational attainment, and geographic location further contribute to delayed diagnoses and poor treatment outcomes. Addressing these barriers, recent initiatives emphasize strategies like telepathology networks, health education programs, and the establishment of cancer support networks to improve early diagnosis and quality of care. This review explores these SDH-based disparities in cancer care within LAC, examining innovative approaches aimed at reducing health inequities and improving outcomes for underserved populations. Through targeted interventions, the article highlights the critical need for policies promoting equitable access to cancer care as a fundamental public health objective in LAC.